Physical inactivity and excessive sucrose consumption are associated with higher serum lipids in subjects with Taq1B CETP polymorphism - Campos‐Perez, W.; Perez‐Robles, M.; Torres‐Castillo, N.; Rodríguez‐Reyes, S. C.; De la Cerda Trujillo, L. F.; Navarro‐Muñiz, E.; Lopez‐Lizárraga, C. R.; Llamas‐Covarrubias, I. M.; Martinez‐Lopez, E. (Journal of human nutrition and dietetics, 2020)
Background Dyslipidaemias result from the interaction between genetic and environmental factors, including diet disequilibrium and physical inactivity. Among the genetic factors associated with serum lipids, the Taq1B CETP polymorphism has been investigated. The B1 allele has been considered as a risk factor for dyslipidaemia because of its association with greater CETP levels and higher serum triglycerides. The present study aimed to determine the role of the Taq1B polymorphism with lipid and anthropometric variables and its interaction with diet and physical activity. Methods In total, 215 subjects were enrolled in this cross‐sectional study. Diet intake was evaluated using a 3‐day food consumption record and physical activity was determined in accordance with World Health Organization recommendations. The Taq1B CETP polymorphism was determined by allelic discrimination. Results Subjects with the B1B2/B2B2 genotype, who had a sucrose consumption ≥5% of the total kcal day−1, had higher levels of total cholesterol (TC) [165.55 (142.21–188.89) mg dL−1 versus 200.19 (184.79–215.60) mg dL−1; P for interaction = 0.034] and low‐density lipoprotein [99.29 (75.52–123.05) mg dL−1 versus 128.64 (113.59–143.69) mg dL−1; P for interaction = 0.037] than subjects with the B1B1 genotype. Subjects who did not perform physical activity and had the B1B2/B2B2 genotype showed significantly higher levels of TC [177.48 (161.36–193.60) mg dL−1 versus 194.49 (185.43–203.56) mg mL−1; P for interaction = 0.033] than subjects with the B1B1 genotype. Conclusions We provide evidence that subjects with inadequate environmental factors carriers of the polymorphic genotype had higher serum lipid levels than subjects with the B1B1 genotype. Subjects with the B1B2/B2B2 genotype who had a sucrose consumption ≥5% of the total kcal/day, had higher levels of total cholesterol and low‐density lipoprotein than B1B1. Subjects who did not perform physical activity and had the B1B2/B2B2 genotype showed significantly higher levels of total cholesterol than subjects with the B1B1 genotype